Euconnus octosetosus Franz transferred to Plaumanniola Costa Lima: implications for the systematics of Scydmaeninae (Coleoptera: Staphylinidae) - Jałoszyński, Paweł (Zootaxa, 2016)
Euconnus octosetosus Franz (Brazil) is demonstrated to show diagnostic characters of the enigmatic genus Plaumanniola Costa Lima. Although this intriguing beetle is much more slender than previously known Plaumanniolini, it differs from Plaumanniola merely in the hypostomal ridges connected mesally and a loose structure of the antennal club. Euconnus octosetosus is transferred to Plaumanniola, resulting in P. octosetosa (Franz) comb. n. Comparative study shows gradual transformations of presumably defensive structural adaptations in Plaumanniola, suggesting evolution from a slender Euconnus-like ancestor to species with a strongly broadened body. Plaumanniola octosetosa is most slender of all species, with long and loosely assembled antennae and weakly flattened legs, whereas P. sanctaecatharinae Costa Lima and P. regina Jałoszyński show most derived characters; these beetles are morphologically adapted to curl in a ball. Plaumanniola simplicisima Jałoszyński represents an intermediary body form. Plaumanniolini Costa Lima is placed as a junior synonym of Glandulariini Schaufuss (= Cyrtoscydmini Schaufuss). A revised diagnosis of Plaumanniola and an overview of the current systematics of Scydmaeninae are given.